2010
DOI: 10.1248/cpb.58.1461
|View full text |Cite
|
Sign up to set email alerts
|

Microemulsions for Intravesical Delivery of Gemcitabine

Abstract: The objective of this work was to develop a safe and effective delivery vehicle for topical treatment of gemcitabine. The physicochemical properties, drug release rate, drug level in plasma and bladder, and histological changes of tissue after drug administration were investigated. The electrical conductivity, mean size, and viscosity of drug-loaded microemulsions were 0.8-102.0 mS/cm, 116.8-322.5 nm, and 42.9-105.0 cps؋10 3 , respectively. Gemcitabine loaded microemulsions showed a slower and sustained releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…The best formula was the hydrophobic delivery, MEb10+, which increased the mortality of the cells when compared with all of the drug formulas. Tsai et al (2010) produced three GEM-loaded-ME formulas that release GEM at different rates depending on the fraction of the ME components. The release rates of MEa, MEb, and MEc were 630.1 55.0, 390.3 96.2, and 141.1 9.6 mg cm 2 h 1/2 , respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The best formula was the hydrophobic delivery, MEb10+, which increased the mortality of the cells when compared with all of the drug formulas. Tsai et al (2010) produced three GEM-loaded-ME formulas that release GEM at different rates depending on the fraction of the ME components. The release rates of MEa, MEb, and MEc were 630.1 55.0, 390.3 96.2, and 141.1 9.6 mg cm 2 h 1/2 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is worth noting that a phase II study of intravesical GEM dissolved in alkaline solution demonstrated that GEM underwent crystallization under certain conditions, high pH, addition of sodium bicarbonate and storage at low temperature, which minimized the amount of GEM subjected into the syringes (Manners et al 2011). The objective of the present study was to evaluate the ME formulations, designed by Tsai et al (2010), in vitro. The ME formulas consisted of isopropyl myristate (IPM) as the oil phase, a surfactant mixture of polyoxyethylene sorbitan monooleate (tween 80) and sorbitan monolaurate (span 20), and an aqueous phase of distilled water and cosurfactant of ethanol.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Phospholipid, ethyl oleate, glycerol and pluronic F68 are biocompatible components of the Tan ME that can be safely used for i.v. injection (16,17). The surfactant enhances the permeability of the ME.…”
Section: Discussionmentioning
confidence: 99%